2019
DOI: 10.3390/nu11040750
|View full text |Cite
|
Sign up to set email alerts
|

Associations of ADIPOQ and LEP Gene Variants with Energy Intake: A Systematic Review

Abstract: This systematic review aims to evaluate the association of adiponectin (ADIPOQ) and leptin (LEP) gene variants with energy intake. Cross-sectional, cohort, and case–control studies that reported an association of leptin and/or adiponectin gene variants with energy intake were included in this review. Human studies without any age restrictions were considered eligible. Detailed individual search strategies were developed for each of the following bibliographic databases: Cochrane, Latin American and Caribbean C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
2
8
0
1
Order By: Relevance
“…4,5,20 The rs17300539 adiponectin gene, an adipokine abundantly produced by adipose tissue, was associated with a decrease in the serum expression of adiponectin in adults. 7,22 In our study, this decrease was also observed in obese children and adolescents. Adiponectin participates in energy homeostasis and acts on adipose tissue, and reduction in adiponectin concentrations promotes sluggish lipid and carbohydrate metabolism, thereby stimulating the consumption of food for energy supply.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…4,5,20 The rs17300539 adiponectin gene, an adipokine abundantly produced by adipose tissue, was associated with a decrease in the serum expression of adiponectin in adults. 7,22 In our study, this decrease was also observed in obese children and adolescents. Adiponectin participates in energy homeostasis and acts on adipose tissue, and reduction in adiponectin concentrations promotes sluggish lipid and carbohydrate metabolism, thereby stimulating the consumption of food for energy supply.…”
Section: Discussionsupporting
confidence: 79%
“…necessary to investigate this relationship in children and adolescents with these polymorphisms and measure the consequences on body weight and health. [5][6][7] Therefore, the objective of this study was to compare anthropometric, biochemical, and hormonal parameters and the presence of genetic polymorphisms of leptin, adiponectin, and TNF-α among eutrophic and obese children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin regulates several metabolic processes, including glucose homoeostasis and fatty acid oxidation (1) . The decrease in serum adiponectin concentration mediated by genetic variation promotes a reduction in the phosphorylation of target proteins by AMP-activated protein kinase (AMPK), which is critical for lipid and carbohydrate metabolism (13,22,48,49) . Therefore, the involvement of the metabolism of many tissues may decrease energy consumption and stimulate food intake (48) .…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, no direct evidence was obtained to support that paternal Zn status could attenuate ME intake and weight gain in female mice, which may be caused by the age and gender variance in mice ( Weigand and Egenolf, 2017 ). Moreover, it was reported that elevated leptin and abrogated adiponectin concentrations may reduce appetite and caloric intake ( Kroll et al., 2019 ), thus it could be inferred that increasing adiponectin and decreasing leptin concentrations may be considered to be a feedback regulation on the negative energy balance. A previous study also showed that paternal ZnD could induce a variety of metabolic abnormalities in liver ( Himoto and Masaki, 2018 ).…”
Section: Discussionmentioning
confidence: 99%